The polymyxin B-induced transcriptomic response of a clinical, multidrug-resistant Klebsiella pneumoniae involves multiple regulatory elements and intracellular targets - Pereira Ramos, Pablo Ivan (2016)
Background: The emergence of multidrug-resistant Klebsiella pneumoniae is a major public health concern. Many K. pneumoniae infections can only be treated when resorting to last-line drugs such as polymyxin B (PB). However, resistance to this antibiotic is also observed, although insufficient information is described on its mode of action as well as the mechanisms used by resistant bacteria to evade its effects. We aimed to study PB resistance and the influence of abiotic stresses in a clinical K. pneumoniae strain using whole transcriptome profiling. Results: We sequenced 12 cDNA libraries of K. pneumoniae Kp13 bacteria, from two biological replicates of the original strain Kp13 (Kp13) and five derivative strains: induced high-level PB resistance in acidic pH (Kp13pH), magnesium deprivation (Kp13Mg), high concentrations of calcium (Kp13Ca) and iron (Kp13Fe), and a control condition with PB (Kp13PolB). Our results show the involvement of multiple regulatory loci that differentially respond to each condition as well as a shared gene expression response elicited by PB treatment, and indicate the participation of two-regulatory components such as ArcA-ArcB, which could be involved in re-routing the K. pneumoniae metabolism following PB treatment. Modules of co-expressed genes could be determined, which correlated to growth in acid stress and PB exposure. We hypothesize that polymyxin B induces metabolic shifts in K. pneumoniae that could relate to surviving against the action of this antibiotic. Conclusions: We obtained whole transcriptome data for K. pneumoniae under different environmental conditions and PB treatment. Our results supports the notion that the K. pneumoniae response to PB exposure goes beyond damaged membrane reconstruction and involves recruitment of multiple gene modules and intracellular targets.